Training to Build Students' Self-Awareness to Improve Qualities in Facing the Digital Era - Rajagukguk, Djudjur Luciana; Salim, Agus; Muhammad, Yusuf; Ramadhanis, Tamara (Indonesian Journal of Community Services Cel, 2023)
The digital era encourages students to be able to adopt something innovative, collaborate, and build a wide network. Utilizing all digital opportunities to provide quality and find inspiration from creative sources. Aims of the service carried out is training to build students' self-awareness to improve quality in facing the digital era at SMKN 3 Depok. The service method is carried out by giving a pre-test to find out whether students understand self-awareness in improving their self-quality. After that, the material was given using Power Point Presentation, then a simulation was held, then questions and answers. After that, students complete a post test to find out that students understand the material that has been given. According from the results of the post test completed by the students, 90% students have knowledge about self-awareness to develop themselves in the digital era. As a result of this workshop, it is hoped that students will further improve student’s quality and be confident that students are able to make themselves more qualified. So that students will be more active in studying, more accepting of their place of study, and have the mindset to develop their own potential in order to be able to bring the environment to a higher quality in the digital era.